VYODIA untuk Pengelolaan Hipertensi pada Pasien Hemodialisis - Udayani, Ni Wayan; Marwati, Marwati; Putra, I Made Agus Widiana (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2026)
Hypertension among hemodialysis patients is a serious health concern, with a prevalence of 34.1%, increasing the risk of cardiovascular disease, renal complications, and economic burden. Suboptimal management of hypertension may lead to a decline in patients’ quality of life. This study aims to develop a mobile application, VYODIA-App, which provides personalized yoga video interventions to assist hemodialysis patients in managing blood pressure. The application was developed using the Behaviour Change Wheel framework to analyze factors influencing patients’ behavioral changes in engaging with yoga therapy, and the Successive Approximation Model, applied iteratively to ensure that the application meets user needs. Usability testing using the System Usability Scale involving 32 respondents yielded a score of 77.1, indicating good user acceptability, although there remains room for improvement in interface design and response speed. The application addresses identified barriers by offering educational modules to enhance users’ understanding of yoga, providing time flexibility through automated reminders, and incorporating anonymity features to increase motivation. Supportive policies for mobile application use in healthcare settings, along with training for healthcare professionals, are also considered essential for successful implementation.